Protective effect of pristine C60 fullerene nanoparticle in combination with curcumin against hyperglycemia-induced kidney damage in diabetes caused by streptozotocin - Demir, Ersin; Aslan, Abdullah (Wiley, 2020)
The present study aims to examine the protective effects of C60 fullerene (C60), Curcumin (CUR;Curcuma longa), C60 + CUR combination against oxidative stress, apoptosis, and changes in cellular level in kidney tissue of diabetic rats. Treatment practices were administered separately to groups for 8 weeks following the approval of diabetes induction. It was observed that the treatment groups had increased antioxidant potential, decreased oxidative stress levels, decreased cholesterol, alpha tocopherol, retinol levels along with improved important changes in fatty acid metabolism compared with the diabetic group. C60, CUR, and C60 + CUR were also determined to act in the direction of reducing kidney damage by activating apoptotic pathways. It can be concluded based on these findings that C60, CUR, and especially C60 + CUR combination has beneficial properties in maintaining kidney tissue and function by effectively preventing oxidative stress, apoptotic changes, and changes at the cellular level in kidney tissue under hyperglycemia conditions. Practical applications C60 and CUR have various biological activities which can be indicated as antioxidant, anti-inflammatory, anticancer, neuroprotective, and hepatoprotective. It has been reported that C60 and CUR protect the cells against oxidative injury brought about by reactive oxygen species (ROS). Data acquired from the present study puts forth that C60 and C60 + CUR may be promising agents to prevent damage induced by hyperglycemic conditions in kidney tissue.
Keywords: apoptosis; C60 fullerene; curcumin; fat-soluble vitamins; lipotoxicity; oxidative stress